PENGARUH DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN(STUDI PADA DEPARTEMEN TEKNIK PT PELINDO MARINE SERVICE) - ZAHROTUL UMMAH, VIA (Jurnal Ilmu Manajemen (JIM), 2017)
Human resources (HR) is important for the company because it has a role as a potential driver of all activities of the company. Companies that have qualified human resources can easily integrate company vision with company goals to employees so thatachievement of corporate goals can be achieved. This study aims to analyze the effect of work discipline and motivation on employeeperformance (Study on engineering department of PT Pelindo Marine Service). The approach used in this research is quantitativeapproach. The sample technique used in this study is using a saturated sample of 42 employees. Data analysis techniques usedmultiple linear regression analysis with the help of SPSS 18 software.The results showed that work discipline posiif significant to the performance of employees with a value of 2.603, the motivation has asignificant positive effect on employee performance with a value of 3.191. Work discipline and motivation simultaneously affectemployee performance. In the test results coefficient of determination (R) obtained value of 0.450. This means that the influence ofwork discipline and motivation on employee performance is 45%, while the remaining 55% is influenced by other factors notexamined in this research. Keywords: Work Discipline, Motivation, Employee Performance.